Experimental study on propagation attenuation characteristics of UWB electromagnetic wave in different coal and mixed media - Xuezhao ZHENG; Yuan HUANG; Ziyu SUN; Jun GUO; Duo ZHANG; Guobin CAI; Xin TONG (Meitan kexue jishu)
Personnel search and localization constitute the fundamental aspects of mine rescue operations. Ultra-Wide Band (UWB) radar technology possesses the capability to penetrate non-magnetic media, including masonry walls, coal, and rock, thereby enabling the detection and localization of individuals beyond physical obstructions. It is anticipated that UWB radar detection technology will address the challenges associated with personnel detection and localization within sheltered mine environments. In order to clarify the attenuation characteristics of UWB electromagnetic wave in coal and rock medium, based on electromagnetic wave propagation theory, the effective propagation distance and attenuation coefficient of electromagnetic wave in coal and rock medium are derived, and it is concluded that the attenuation coefficient of UWB electromagnetic wave in the environment of lossy medium is positively correlated with the relative dielectric constant and conductivity of medium. And utilize the RF signal attenuation system to carry out the propagation attenuation test of UWB electromagnetic wave in four thicknesses (30, 60, 90, 120 cm) of lignite, lean coal, sandstone, limestone and coal-rock mixing (mixing ratios of 3∶7 and 7∶3) media. The test results show that: ① UWB electromagnetic wave energy are reduced with the increase of the thickness of the coal rock medium, the electromagnetic wave energy amplitude waveform in the medium will produce a number of intervals close to the oscillation, and the reduction in the magnitude of the sequential decrease, indicating that the UWB electromagnetic wave energy attenuation is positively correlated with the thickness of the coal rock medium. ② The attenuation of electromagnetic wave energy in coal and rock stratified mixed media depends on the attenuation of coal and rock media and the ratio of coal and rock, the attenuation of electromagnetic wave in coal and rock mixed media is similar to the superposition of the attenuation of a single coal and rock media, which is positively correlated to the degree of electromagnetic wave attenuation penetrating the stratified mixed coal and rock media with the degree of attenuation of electromagnetic wave in a single medium of coal and rock, as well as the ratio of coal and rock. ③ The energy peak of UWB electromagnetic wave is shifted to the low-frequency region with the increase of coal rock thickness. Under different thicknesses, the UWB electromagnetic wave penetrating the coal-rock medium has energy peaks corresponding to the low-frequency frequency, in which the UWB electromagnetic wave penetrating the 120 cm lean coal and lean coal sandstone, lean coal limestone mixed medium has two peaks with the same peaks in the low-frequency region and at the center frequency, which indicates that there are multiple optimal detection frequencies in the coal-rock medium with a weak attenuation amplitude. The test results can provide a reference for the basic research related to UWB radar life information detection technology and equipment development and application for mine rescue.